Telomerase mRNA Enhances Human Skin Engraftment for Wound Healing - Chang, David F.; Court, Karem A.; Holgate, Rhonda; Davis, Elizabeth A.; Bush, Katie A.; Quick, Andrew P.; Spiegel, Aldona J.; Rahimi, Maham; Cooke, John P.; Godin, Biana (Advanced healthcare materials, 2024)
Deep skin wounds represent a serious condition and frequently require split‐thickness skin grafts (STSG) to heal. The application of autologous human‐skin‐cell‐suspension (hSCS) requires less donor skin than STSG without compromising the healing capacity. Impaired function and replicative ability of senescent cutaneous cells in the aging skin affects healing with autologous hSCS. Major determinants of senescence are telomere erosion and DNA damage. Human telomerase reverse transcriptase (hTERT) adds telomeric repeats to the DNA and can protect against DNA damage. Herein, hTERT mRNA lipid nanoparticles (LNP) are proposed and evaluated for enhancing cellular engraftment and proliferation of hSCS. Transfection with optimized hTERT mRNA LNP system enables delivery and expression of mRNA in vitro in keratinocytes, fibroblasts, and in hSCS prepared from donors’ skin. Telomerase activity in hSCS is significantly increased. hTERT mRNA LNP enhance the generation of a partial‐thickness human skin equivalent in the mouse model, increasing hSCS engraftment (Lamin) and proliferation (Ki67), while reducing cellular senescence (p21) and DNA damage (53BP1). Human telomerase reverse transcriptase mRNA lipid nanoparticles (hTERT mRNA LNP) are formulated for improved healing of deep skin wounds using human skin cells suspension (hSCS). Transfection with optimized hTERT mRNA LNP enables delivery and expression of mRNA in hSCS in vitro. hTERT mRNA LNP‐treated hSCS enhances skin regeneration in partial‐thickness human‐skin equivalent in mice, increasing hSCS engraftment/proliferation, while reducing senescence/DNA‐damage.